The Transgressive Literacy of the Comic Maidservant in Tobias Smollett’s Humphry Clinker - Kathleen Tamayo Alves (Akademisk Kvarter, 2011)
Kathleen Alves' article The Transgressive Literacy of the Comic Maidservant in Tobias Smollett's 'Humphry Clinker' returns us to social tensions by discussing the "servant problem" in Tobias Smoellett's Humphry Clinker, where servants are revealed to not exist as external subjects but instead as attendants in the discursive formation of the modern family.